Cardio-Chemical Exchange Saturation Transfer Magnetic Resonance Imaging Reveals Molecular Signatures of Endogenous Fibrosis and Exogenous Contrast Media. (January 2015) - Vandsburger, Moriel; Vandoorne, Katrien; Oren, Roni; Leftin, Avigdor; Mpofu, Senzeni; Delli Castelli, Daniela; Aime, Silvio; Neeman, Michal
<x xml:space="preserve">Abstract</x> Background— Application of emerging molecular MRI techniques, including chemical exchange saturation transfer (CEST)-MRI, to cardiac imaging is desirable; however, conventional methods are poorly suited for cardiac imaging, particularly in small animals with rapid heart rates. We developed a CEST-encoded steady state and retrospectively gated cardiac cine imaging sequence in which the presence of fibrosis or paraCEST contrast agents was directly encoded into the steady-state myocardial signal intensity (cardioCEST). Methods and Results— Development of cardioCEST: A CEST-encoded cardiac cine MRI sequence was implemented on a 9.4T small animal scanner. CardioCEST of fibrosis was serially performed by acquisition of a series of CEST-encoded cine images at multiple offset frequencies in mice (n=7) after surgically induced myocardial infarction. Scar formation was quantified using a spectral modeling approach and confirmed with histological staining. Separately, circulatory redistribution kinetics of the paramagnetic CEST agent Eu-HPDO3A were probed in mice using cardioCEST imaging, revealing rapid myocardial redistribution, and washout within 30 minutes (n=6). Manipulation of vascular tone resulted in heightened peak CEST contrast in the heart, but did not alter redistribution kinetics (n=6). At 28 days after myocardial infarction (n=3), CEST contrast kinetics in infarct zone tissue were altered, demonstrating gradual accumulation of Eu-HPDO3A in the increased extracellular space. Conclusions— cardioCEST MRI enables in vivo imaging of myocardial fibrosis using endogenous contrast mechanisms, and of exogenously delivered paraCEST agents, and can enable multiplexed imaging of multiple molecular targets at high-resolution coupled with conventional cardiac MRI scans.